Analisis Penerapan Akuntansi Syariah Berdasarkan Psak Nomor.102 Pada Pembiayaan Murabahah Di Bmt Al-Ittihad Cikurubuk Tasikmalaya - Joni Ahmad Mughni (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2019)
Background problem in this study high financing activity and selling based on murabaá¸¥ah KSPPS BMT Al-Ittihad murabaá¸¥ah where the transaction is done more than 97% of all the transactions carried out. While the goal in this research is to know the application of accounting and financing Murabaha on BMT Cikurubuk Al-Ittihad. And to analyse the suitability of the accounting application of financing illegal murabaha with PSAK No. 102 on BMT Cikurubuk Al-Ittihad. The research method used was qualitative approach. Data collection techniques used by authors was an interview ansd documentation. Data analysis techniques using descriptive analysis. The research found that the recognition and measurement of assets, receivables, murabaha murabaha profit installment, pieces of murabaha murabaha, and fines already in accordance with PSAK NO. 102. Presentation of KSPPS applied by the BMT Al-Ittihad is in compliance with PSAK NO. 102, i.e. accounts receivable balance of murabaha served on the net that can be realized, the advantage of murabaha is presented in the income statement and profit murabahah deferred interest is served in the balance sheet but note with reserve losses of accounts receivable.